Runne-Beana: Dog Herds Ethnographer - Anderson, Myrdene (Ethnobiology Letters, 2016)
Saami society in Lapland (now often called Saapmi), particularly the seasonally-nomadic reindeer-breeding sector, is predicated upon mobility and autonomy of its actors. Runne-Beana, a talented reindeer-herding dog, exhibited both mobility and autonomy when allocating to himself a peripatetic ethnographer, on the first day of five years of doctoral dissertation fieldwork in arctic Norway in 1972. That family’s and the wider community’s reactions to Runne-Beana’s behavior, and mine, highlight the tensions when mobility and autonomy compound with ideologies of ownership and control. At the same time, his companionship profoundly shaped all field relationships, engendering an understanding of dog culture as it is manifest in the herder/herding dog/reindeer triad and in the interpenetration of assumptions concerning child/dog enculturation.